PENGARUH SUMBER DAYA MANUSIA SERTA PARTISIPASI ANGGARAN TERHADAP KINERJA SATKER PADA BPLJSKB BEKASI - Merintan Berliana Simbolon; Angelina Wahyu Christyani (Jurnal Publikasi Ekonomi dan Akuntansi, 2022)
Financial Management in Indonesia has undergone many changes or improvements along with the spirit of government financial management reform. It is marked by the issuance of financial regulations and its derivatives. The problem that exists until now is the difficulty to determine benchmarks that can be used to measure the performance of government agencies comprehensively through budgets that have been prepared. Human Resource Competence is one of the important factors that can determine the successful implementation of a financial management system in each Regional Device Work Unit / Agency so that improving the quality of human resources managers is something that must be implemented. For this reason, research is needed that can explain the relationship between the Influence of Human Resources and budget participation both partially and simultaneously on performance at the Road Testing And Motor Vehicle Certification Center. The study was conducted with a causal associative method with the aim of finding out the relationship between two or more variables and the time dimension of this study is a cross sectional involving many data samples at a time. For data collection techniques using questionnaire techniques to 50 (fifty) people. The results of the study concluded that at the Road Testing and Motor Vehicle Certification Center for HR Variables and Budget Participation partially and simultaneously significantly affect satker performance and variable budget participation affects performance both significantly and positively.